Accounting information systems and internal control - Vaassen, E. H. J. (Eddy H. J.); Meuwissen, Roger; Schelleman, Caren (Hoboken, NJ : John Wiley & Sons, 2009)
The book provides a comprehensive approach to the design and evaluation of internal control systems. It covers both a traditional process approach and a contemporary typology approach that focuses on different types of organisationsal processes.. It is considered an integral and enabler of internal control.. It is written for students at advanced undergraduate and postgraduate levels.
Organizations and their systems -- Internal control -- Bridging the gap between internal control and management control -- The dynamics of control and it -- Documenting and evaluating internal control systems -- Organizational processes -- The purchasing process -- The inventory process -- The production process -- The sales process -- Secondary processes -- Typology of organizations -- Trade organizations -- Production organizations -- Service organizations with a limited flow of goods -- Service organizations that put space and electronic capacity at their customers' disposal -- Service organizations that put knowledge and skills at their customers' disposal -- Governmental and other not-for-profit organizations.
Includes bibliographical references and index.
opc 30/04/13
Loans
Keywords: Accounting -- Data processing; Information storage and retrieval systems -- Accounting